1994
DOI: 10.1111/j.1399-6576.1994.tb04014.x
|View full text |Cite
|
Sign up to set email alerts
|

Thoracic epidural analgesia in aortocoronary bypass surgery II: effects on the endocrine metabolic response

Abstract: Thoracic epidural analgesia (TEA) may offer haemodynamic benefits for patients with coronary heart disease going through major surgery. This may-in part-be secondary to an effect on the endocrine and metabolic response to surgery. We therefore investigated the effect of TEA on the endocrine metabolic response to aortocoronary bypass surgery (ACBS). Thirty male patients (age < 65 years, ejection fraction > 0.5) were randomized into 3 groups; the HF group receiving a high dose fentanyl (55 micrograms.kg-1) anaes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
32
1
1

Year Published

1996
1996
2019
2019

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 95 publications
(38 citation statements)
references
References 28 publications
4
32
1
1
Order By: Relevance
“…Moore found that with TEA there was no increase in B-glu and catecholamine, and cortisol responses were blunted until at least 24 h after CPB [11]. Stenseth showed that TEA blunted and delayed the increase in glucose and cortisol after CABG [12]. Curiously, Richardson showed that continuous paravertabral anaesthesia could prevent hyperglycaemia after a thoracotomy while TEA could not [13].…”
Section: Discussionmentioning
confidence: 95%
“…Moore found that with TEA there was no increase in B-glu and catecholamine, and cortisol responses were blunted until at least 24 h after CPB [11]. Stenseth showed that TEA blunted and delayed the increase in glucose and cortisol after CABG [12]. Curiously, Richardson showed that continuous paravertabral anaesthesia could prevent hyperglycaemia after a thoracotomy while TEA could not [13].…”
Section: Discussionmentioning
confidence: 95%
“…Thirty-one studies were used for measurements of epinephrine, norepinephrine, cortisol, and glucose blood concentrations; for 13 studies there was no information available on blood loss and/or blood transfusion; for nine studies, no patient was transfused; for one study there was no difference in the number of units transfused; and for five studies there was no statistical difference in the amount of estimated blood loss. For three studies there was a statistical difference either in estimated blood loss [10,64] or in intraoperative hematocrit [45]. If these last three studies were excluded from the analysis, the * P < 0.05.…”
mentioning
confidence: 99%
“…(3,4) Epidural analgesia reduces the endocrine and metabolic stress response, facilitates early gut mobility, decreases wound infections and postoperative respiratory complications. (3,(5)(6)(7)(8)(9) Given that epidural catheter insertion is an invasive method associated with complications, and that prostatic cancer patients are older, often with comorbidites, degenerative spine changes and on anticoagulants, this method is often avoided. (10) Only opioid based pain relief is associated with adverse reactions (insufficient breathing, nausea, vomiting, constipation, ileus, drowsiness); also, acute tolerance to opioids may develop intraoperatively.…”
Section: Introductionmentioning
confidence: 99%